2018
DOI: 10.1590/0102-672020180001e1369
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Colorectal Cancer

Abstract: Introduction: Colorectal cancer is a very frequent sort of neoplasm among the population, with a high mortality rate. It develops from an association of genetic and environmental factors, and it is related to multiple cell signaling pathways. Cell cultures and animal models are used in research to reproduce the process of disease development in humans. Of the existing animal models, the most commonly used are animals with tumors induced by chemical agents and genetically modified animals. Objective: To presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
0
30
0
2
Order By: Relevance
“…Therefore, nitrites are the active ingredient and nitrates serve as reservoirs that supply nitrites. There are numerous epidemiological studies that associate the potential risk of gastric cancer and other cancers with the intake of nitrates, nitrites and nitrosamines in the diet 15,17,[19][20][21] .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nitrites are the active ingredient and nitrates serve as reservoirs that supply nitrites. There are numerous epidemiological studies that associate the potential risk of gastric cancer and other cancers with the intake of nitrates, nitrites and nitrosamines in the diet 15,17,[19][20][21] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In recent decades, most experimental studies have been carried out on mammals, due to their similarities with humans, in many ways. The conclusions of studies on animals, respecting ethical aspects, cannot be fully transposed to humans 18,20 . The results of this study again confirmed that the lesions are due to the presence of duodenogastric reflux.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Each animal model has its pros and cons—Table 1, and in some cases, association of more than one form in CRC induction is necessary . The model should be chosen accordingly to the study expectations and aim, maximizing its potential …”
Section: Conclusion/final Considerationsmentioning
confidence: 99%
“…Его используют для моделирования рака толстой кишки у лабораторных животных [3,4]. Эта модель достаточно изучена [5][6][7], она в отличие от клеточных культур позволяет воспроизводить опухолевый ангиогенез и метастазирование [8]. Известно, что опухоль, растущая под действием ДМГ, приводит к развитию акцидентальной инволюции тимуса [9], а также к морфологическим изменениям в органах эндокринной системы [10].…”
Section: Introductionunclassified